LITERASI DIGITAL MARKETING BAGI UMKM DESA WARINGINJAYA - Muhammad Fajar Oktara; Muchammad Al-Fatih; Devi Amalia; Eka Nurfaidah; Purwanti Purwanti (CV. Denasya Smart Publisher, 2025)
Community Service Program (KKN) is a concrete manifestation of the Tri Dharma of Higher Education, which aims to encourage students to participate directly in community development. The KKN activity, held in Waringinjaya Village, Kedungwaringin District, Bekasi Regency, carried the theme